From praxis to pragmatism: Junior scholars and policy impact. Issue 4 (2nd October 2019) - Ali, Christopher; Herzog, Christian
ABSTRACT: Drawing on Buckingham's observation that academic research either has to become public knowledge or its originators must have a high visibility in the public realm before their research can find inclusion into policymaking processes, this article offers a variety of examples of how academics have managed to bridge the gap between media and communication policy scholarship and policymaking. Contrary to the long-standing belief that policy impact is extremely difficult and rare to achieve, we argue that junior scholars have many opportunities to have their work become part of the policymaking process through new forms of conversation, collaboration, coalition-building, changing perceptions of public knowledge, and a more conceptual understanding of impact.